Deconstructing age(s): an analysis of the different conceptions of age as a legal criterion for access to assisted reproductive technologies. Issue 2 (15th December 2022) - Martani, Andrea; De Clercq, Eva; De Geyter, Christian; Pennings, Guido; Wangmo, Tenzin; Elger, Bernice Simone
Abstract: Whether there should be restrictions for access to Assisted Reproductive Technologies (ART) is a matter of continuous medical, societal, and ethico-legal debate. One of the most controversial topics in this context is the use of parental age as a criterion to limit access to ART. Views are divided on whether there should be an upper age limit for one or both parents and on where such limits should be. Although this debate is centered around the issue of 'age' and although age -related limits are present in many legislations, the intrinsic ambiguity of the term `age' is largely overlooked. In this article, we build on gerontological, medical, and sociological literature on the concepts of 'age' and 'aging' to distinguish three conceptions of age that are relevant for ART regulation: the chronological, the biological, and the social-cultural one. Beyond mapping out these conceptions of age, we describe how they relate to ART and reproduction, and illustrate the advantages and disadvantages of relying on each of them as a basis for limiting ART access. Finally, we propose a template for defining legal age limits for ART access in the law, based on the refined understanding of the different conceptions of age that we outline and we discuss two potential objections to our proposal.